Critical Animal Studies : An Introduction - McCance, Dawne, 1944- (Book collections on Project MUSE., 2013)
"Having roots as a specialized philosophical movement at Oxford University in the early 1970s, critical animal studies is now taking shape as a wide-open, multidisciplinary endeavor through which scholars across the humanities, sciences, and social sciences, and others ranging from creative writers to architects, are joining together to address issues related to today's unprecedented subjection of animals. Introducing this emerging field, Dawne McCance describes the wide range of analysis and approaches represented, looking at much-debated practices such as industrialized or "factory" farming of animals, handling and slaughter, animal experimentation, wildlife management, animal captivity, global genomics, meat-eating, and animal sacrifice. McCance equally focuses on many of the theoretical and ethical problems that recur across the field, raising critical questions about prevailing approaches to animal ethics, and inviting new ways of thinking about and responding to animals."--Publisher's website